PENERAPAN MANHAJ TERHADAP PENGUATAN FIKIH KADERISASI ULAMA PONDOK PESANTREN ASâADIYAH SENGKANG - Muchsin, Agus (Jurusan Syariah dan Ekonomi Islam Institut Agama Islam Negeri (IAIN) Parepare, 2016)
This paper discusses about the tradition of fiqh Madzhab in manhaji in scholars regeneration at Islamic boarding schools Asâadiyah Sengkang. The focus of the study is the fiqh construction of Maâhad al-Aliy and implementation of Mahad al-Qaeda Usuliyah in strengthening fiqh Maâhad al-Aliy at Islamic boarding schools Asâadiyah Sengkang. The approach of this study is a qualitative descriptive approach. It is concluded that the fiqh construction of Islamic boarding school Asadiyah is determined by scholars because they have full authority to lead and to determine the reference books of jurisprudence at the school. Then, the application of the methodology of fiqh can be seen in the use of the rules: (1) fiqhiyah; al-Umuru bi maqashidiha regard to the intention of ablution, (2) lughawiyah; in terms of mulamasah and permissibility mengqashar and shorten pray only for those on trip by using using Zahir meaning, not Majazi, and (3) ushuliyah in the distribution of tithes to eight asnaf.